Equine UDP-glucuronosyltransferases and their role in phase II metabolism - Pickwell, Natalie Dawn (2018)
Metabolism is an essential chemical process and pathway involving multiple reactions. Oxidative or functionalisation reactions dominate phase 1 metabolism and is predominately controlled by the Cytochrome P450s (P450s). Phase 2 reactions are frequently referred to as the detoxification, or elimination, phase. Several families of enzymes are involved, and the largest of these are the Uridine diphosphate 5’-glucuronosyltransferases (UGTs). The purpose of this project was to initiate the development of an equine in vitro toolbox, concentrating on the UGTs. This required identification of UGTs in the equine genome. The first step used syntenic analysis which enabled us to utilise relative gene order conservation between species to determine whether the predicted gene encoded a member of the UGT superfamily. Further analysis of sequence relationships provided confidence that the genes under investigation were UGTs, but also allowed us to determine which UGT orthologue we were investigating. PCRs were performed to isolate the genes, and subsequent sequencing enabled the UGTs to be investigated for key features, including signal peptides, signature sequences, transmembrane domains, and dilysine repeats, which are characteristic of this family of membrane-bound proteins. We isolated and characterised five putative equine UGTs. Subsequent analyses indicated these to be orthologous to human UGT1A6, UGT2A3, UGT2B17, and two UGTs orthologous to UGT3A2. Three equine UGT genes were cloned into a vector for the development of functional recombinant proteins. UGT1A6, UGT2A3 and UGT3A2 expression constructs were transfected into Human Embryonic Kidney 293 cells and stable cell lines generated for analysis. Four drugs were assayed to determine the functionality of the recombinant enzymes and individual substrate specificities. Whilst these studies were inconclusive, further work is required to establish function and substrate profile in order to take the first steps towards creating an in vitro toolbox for equine drug metabolism. Expression of UGT1A6 and UGT3A2 was measured in four tissue samples from 12 horses. For both genes, expression levels in the liver were greatest whilst the brain showed negligible expression. Expression levels of both genes in the kidney and lung were similar and lower than levels detected in the liver.